Conceptual and terminological apparatus of research into the pedagogical concept of education of future teachers in the conditions of digitalization of education - Prokopenko, A. (Problems of Engineer-Pedagogical Education, 2023)
In the scientific article the author analyzes and clarifies the conceptual and terminological apparatus of research into the pedagogical concept of education of future teachers in the conditions of digitalization of education. The author of scientific research presents the basic principles of the study and defines the key concept of "pedagogical concept of education of future teachers in the digitalization of education." It has been proven that tutoring can be considered an important and integral part of the education process, the main task of which is to promote the personal and professional potential of the subjects of the process, but the tutor is its key figure. It was found that the term "coaching" should be understood as a modern technology of coordination of professional activities and education of others, in the process of which there is an increase not only in the effectiveness of professional activities, but also self-esteem in general. The author of the scientific article found that the main function of the coach is to establish a relationship between the "personal trainer" and participants in the education process, directing them to find ways to achieve the desired goals, while developing a certain algorithm for their implementation. In the process of scientific research, the author identified the role of the advisor in the education process, which is to provide advice on choosing optional educational components of higher education, choosing a place of various internships (industrial, undergraduate or pedagogical) and work after graduation. It is quite interesting for the author to find out the functions of the facilitator. In the process of education, the functions of the facilitator are aimed at encouraging, motivating and stimulating students (pupils, students, research and teaching staff) to independently conduct benchmarking and ensure effective communication in a group or team to achieve intellectual comfort for each participant. The author also briefly describes the new educational program, which is curriculum, and the main types of education: formal and informal. According to the algorithm of studying the research problem, the table of definitions of the concept of "digitalization" is given and the concept of "digitalization of education" is specified. In the context of scientific research, it was found that the key concept of "pedagogical concept of education of future teachers in the digitalization of education" should be understood as the avant-garde idea of pedagogical science, which is implemented through the priority direction of the modernization of the educational process, the goal of which is the all-round flourishing of the personality of future teachers in the conditions of the large-scale process of introduction, integration and use of digital technologies and digitized information.